Routledge handbook of feminist peace research - Väyrynen, Tarja; Parashar, Swati; Féron, Élise; Confortini, Catia Cecilia (Routledge, 2021)
This handbook provides a comprehensive overview of feminist approaches to questions of violence, justice, and peace. The volume argues that critical feminist thinking is necessary to analyse core peace and conflict issues and is fundamental to thinking about solutions to global problems and promoting peaceful conflict transformation. Contributions to the volume consider questions at the intersection of feminism, gender, peace, justice, and violence through interdisciplinary perspectives. The handbook engages with multiple feminisms, diverse policy concerns, and works with diverse theoretical and methodological contributions.
Literaturangaben, Register
Keywords: Electronic books